Swelling clay minerals and containment risk assessment for the storage seal of the Peterhead CCS project. (March 2020) - Busch, A.; Hangx, S.J.T.; Marshall, J.D.; Wentinck, H.M.
Highlights: Clay swelling can potentially reactivate faults through swelling pressure build-up, leading to leakage from the storage reservoir. A passive safeguards procedure shows that this leakage mechanism is unlikely for the Peterhead CCS project. While the amount of smectite is high enough, possible sub-seismic fault offsets would disallow this leakage mechanism. Mudrock plasticity, especially for high smectite rocks is considered as a passive safeguard limiting swelling pressure build-up. Abstract: Coupled modelling, based on laboratory data, indicated that the storage seal above the Captain reservoir of the Peterhead CCS project could be affected by stresses caused by clay swelling due to CO2 interaction. In particular, calculations indicate that, over a period of 100 – 10, 000 years, local shear failure in rock exposed to CO2 may occur under unfavourable stress conditions. The likelihood and consequences of local shear failure are however difficult to assess. We therefore defined passive safeguards against this potential risk to seal integrity. The basis for these safeguards is data and information given in the Peterhead CCS Storage Permit Application (storage seal thicknesses, lithologies, reservoir conditions etc.), chemical, thermodynamic and mechanical data from laboratory measurements, as well as the coupled model built and described earlier by Wentinck and Busch (2017). The passive safeguards provided in this study address the mineralogy of the caprock and more specifically its swellable clay content. Furthermore, the geometry of the reservoir is addressed, particularly with respect to the presence of pre-existing faults. Our model shows that for shear failure to be a risk a fault offset on the order of the thickness of the sealing layer needs to be present and in contact with the CO2 plume. It should be noted that swelling stress build-up may relax by creep of the surrounding shale matrix, thereby buffering this effect. Finally, the risk of CO2 to escape the storage container only exists when slip on pre-existing faults leads to permeability enhancement as well as reduction of capillary entry pressures along the fault. Our analyses show that the smectite contents of the unit at the base of the caprock is significant with an average of 57 %, substantiating the threat of clay swelling. Taking the locations of interpreted faults and the total storage seal thickness of 117−165 m, we find no potential offsets similar to this thickness, as identified offsets are up to 33 m. Unquantified uncertainties remain in the creep behaviour of the caprock as well as the fault permeability. Given however that a maximum fault offset is lower than the seal thickness, we classify loss of containment due to fault reactivation caused by swelling clays, and concomitant fluid leakage, to be a low geological risk for the Peterhead CCS project.